Islamic Banking Efficiency in Indonesia and Malaysia: Two Stages Data Envelopment Window Analysis - Pantas, Pribawa E; Susetyohadi, Agus; Azwita, Laurin (Universitas Negeri Surabaya, 2021)
This study aimed to evaluate the efficiency of Islamic banks in Indonesia and Malaysia and examine the determinants of their efficiency in 2015-2019 using a two-stage data development window analysis approach. The research involves 13 Indonesian Islamic banks and 16 Malaysian Islamic banks. The first test step using the Data Envelopment Window Analysis (DEWA) approach has shown that the Islamic Bank's efficiency in managing resources is inefficient. The second research process using the Tobit model shows that the Capital Adequacy Ratio (CAR), Return on Asset (ROA), Non-Performing Financing (NPF), and Deposit Ratio Financings (FDR) do not have a significant impact on the efficiency of Indonesian Islamic Banking. Though CAR has significant positive effects on banking efficiency in Malaysia, NPF has a significant impact on Malaysian Islamic banks' efficiency. This study implies that the banking industry players increase their efficiency, mainly to enhance the amount of finance directed more towards the production sector, to increase the Islamic banking industry's market share in both countries.